2014
DOI: 10.4103/2141-9248.141964
|View full text |Cite
|
Sign up to set email alerts
|

A survey of characteristics of self-immolation in the northern Iran

Abstract: Background:Suicide is an action deliberately initiated and performed by a person with complete awareness of its fatal outcome, prevalence of which is very rare in developed countries, but it is reported with more frequency in Middle East including Iran.Aim:This study was carried out to analyze the characteristics, mortality, and related factors of burned patients who attempted to suicide by self-immolation in Northern Iran.Materials and Methods:In this retrospective study, the archived files of 101 cases that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In the meta-analysis the case fatality rate of self-immolation in Iran was estimated to be 62.1%. Previous studies have reported it as ranging from 50 to 90% [40, 50, 51]. The rate is reported to be 27% in Sri Lanka, 84.95% in Pakistan, and 79% in Eastern Mediterranean Region [44, 47, 52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the meta-analysis the case fatality rate of self-immolation in Iran was estimated to be 62.1%. Previous studies have reported it as ranging from 50 to 90% [40, 50, 51]. The rate is reported to be 27% in Sri Lanka, 84.95% in Pakistan, and 79% in Eastern Mediterranean Region [44, 47, 52].…”
Section: Discussionmentioning
confidence: 99%
“…Study of Ramim et al ., (2013) among patients of a burns ward in Tehran, Iran found that 94% of the self-immolation cases had introduced the physical and verbal violence as the cause of their action [57]. Size of the Family, birth order of children, and problems in relation of spouses are the other risk factors [51, 58]. The prevention plans should focus on screening programs for mental problems, increasing the access to psychological consultations, training for communication skills -especially in family environments, and improving the knowledge and ability of the younger population for marriage and marital relations.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of self-immolation was 2.8 /100,000 people in our study population; near to 42% of the rate of self-immolations was dropped during the study period. In one study by Ahmadi in Northern Iran the rate of self-immolation was reported 1/100,000 in general population [15]. Therefore, the incidence rate of self- immolation suicide was different in Iranian population depends of geographic areas.…”
Section: Discussionmentioning
confidence: 99%
“…According to the world health organization, suicide cases will reach from 804000 cases in 2012 to 1530000 cases in 2020 (1,2). Prevalence, methods, and concepts of suicide vary based on geographical location, social and cultural factors, and gender (3). Selfimmolation is one of the most painful and significant methods of suicide and indefinable at the same time which exerts high social effect (4).…”
Section: Introductionmentioning
confidence: 99%